Variables of risk management in sports among sports administrators: A mixed method - Chukwurah, L. N.; Badaru, U.; Ngwoke, O. R.; Abbah, O. I. (International Journal of Human Movement and Sports Sciences, 2021)
Risks are inevitable in sports activities and organizations; however, there are increasing occurrences of risks in Nigeria sports organizations in spite of standard risk management process. This study therefore examined socio-demographics determining risks management among sports administrators in Nigeria. Mixed method design was adopted. 150 coaches provided quantitative data by completing a validated questionnaire. 10 interview sessions were conducted among 10 sports administrators for the qualitative data. Pre-tested validated questionnaire and an in-depth interview guide were used for collecting data. Descriptive statistics T-test and ANOVA were used to analyze the quantitative data. Using NVivo 11 pro, qualitative data were coded and thematically analyzed, and data were presented using verbatim quotes. It was found that type of sports (p = > .05), educational level (p = > .05) and job experience (p = > .05) did not exert significant differences on risks management of sports administrators. However, the qualitative data show that majority of the participants view interactions between the variables and application of risks management, which is in line with contingency theory. The findings have implications for the effective risk management in Nigeria sports. Therefore, Nigeria sports governing bodies must demonstrate commitment and establish strong alignments between socio-demographics of sports administrators/managers and practice. These would ensure best practices in sports councils/organizations.